Emergency electrical cardioversion: abnormal discharge synchronization leading to ventricular fibrillation – a case report - Michał P. Pluta; Łukasz J. Krzych (Annales Academiae Medicae Silesiensis)
Ventricular tachycardia is a life-threatening arrhythmia that usually occurs secondary to coronary ischemia or as a result of structural heart disease. Abnormal synchronization can lead to the convers ion of ventricular tachycardia to ventricular fibrillation and subsequent cardiac arrest, which is very rare. The study presents the case of a 56-year-old man in whom abnormal discharge synchronization led to ventricular fibrillation.